2023
DOI: 10.1108/jaar-07-2022-0190
|View full text |Cite
|
Sign up to set email alerts
|

The institutionalisation of social and environmental accounting practices in Europe

Abstract: PurposeIn the last few years, the European context has been characterised by a high degree of attention paid by policymakers, practitioners and academics to the effects related to the transposition of Directive 2014/95/EU by the member states. In particular, one the main issues of the intervention made by the European Commission is represented by the theoretical misalignment between corporate communications and actions. According to this evidence, this paper aims to shed light on this debate through a critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…More relevant to this research is its application in studies examining the effects of MD 61,11 mandatory CSRR on reporting practices. For example, while Pizzi et al (2023) Consistent with these studies, as CSRR has been made mandatory for Malaysian PLCs to comply with since 2007 and given that BMB considers such reporting as one of the listing requirements, institutional theory underpins our study. We focus on coercive pressures to examine the impact of the implementation of SRG 2.0 on the readability of CSRR among Malaysian PLCs.…”
Section: Theoretical Frameworkmentioning
confidence: 82%
See 2 more Smart Citations
“…More relevant to this research is its application in studies examining the effects of MD 61,11 mandatory CSRR on reporting practices. For example, while Pizzi et al (2023) Consistent with these studies, as CSRR has been made mandatory for Malaysian PLCs to comply with since 2007 and given that BMB considers such reporting as one of the listing requirements, institutional theory underpins our study. We focus on coercive pressures to examine the impact of the implementation of SRG 2.0 on the readability of CSRR among Malaysian PLCs.…”
Section: Theoretical Frameworkmentioning
confidence: 82%
“…Furthermore, our study extends the application of institution theory to examine the impact of mandatory regulations on CSRR readability as prior recent studies focus on the overall level of CSRR post regulations (e.g., Jahid et al. , 2023; Pizzi et al ., 2023). Thirdly, it shows the impact of implementing SRG 2.0 on the readability of CSRR among Malaysian PLCs.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The institutional model of collaborative project management includes aspects of relational and contractual management. Change is facilitated by temporal linkages between institutional projects and vertical linkages between institutional projects and sector-level development programs (Pizzi et al, 2023). Hamidu et al (2023) examined the moderating effect of supply chain disruption on the relationship between supply chain flexibility and supply chain efficiency for manufacturing firms in Ghana and showed that SCR has a significant positive effect on SCP.…”
Section: Institutionalization (Inst) and African Continental Free Tra...mentioning
confidence: 99%
“…Nevertheless, the NFRD represents only the first step of a possible path of institutionalization (Pizzi et al, 2023) of sustainability reporting in the European context. The EU has recently approved a new regulation, Directive 2022/2464/EU (CSRD).…”
Section: Introductionmentioning
confidence: 99%